Development and implementation of a web-based continuing professional development (CPD) programme on medical genetics - Kulatunga, G.G.A.K.; Marasinghe, R.B.; Karunathilake, I.M.; Dissanayake, V.H.W. (SAGE, 2013)
We developed, implemented and evaluated a web-based continuing professional development (CPD) programme on medical genetics. Development of the CPD programme followed the ADDIE model, i.e. Analysis, Design, Develop, Implement and Evaluation. An invitation to participate in a needs analysis survey was sent to all doctors on the email list of the Sri Lanka Medical Association. A total of 129 completed surveys was received (57% of the 228 who accessed the online survey). The average age of respondents was 42 years (range 27-81). The male: female ratio was approximately 2 : 1. Almost all respondents (96%) selected web-based CPD programmes, or web-based and conventional lectures, as their preferred method of learning. The programme was piloted on a group of 10 doctors. The average pre-knowledge score was 40.3 and the post-knowledge score was 62.1 marks out of 100 (P ¼ 0.002). We conclude that a web-based CPD programme on medical genetics is feasible in Sri Lanka.
Keywords: continuing professional development (CPD); MEDICINE::Dermatology and venerology,clinical genetics, internal medicine::Clinical genetics::Medical genetics